Non-invasive suppression of essential tremor via phase-locked disruption of its temporal coherence - Sebastian R. Schreglmann (Nature Portfolio, 2021)
Aberrant synchronous oscillations have been associated with numerous brain disorders, including essential tremor. The authors show that synchronous cerebellar activity can casually affect essential tremor and that its underlying mechanism may be related to the temporal coherence of the tremulous movement.